Breves considerações sobre os rituais fúnebres e o processo de luto: Herança cultural e tradição religiosa (Razão e Fé, 2023)
The intent of the article is to present a brief introduction about cultural heritage and religious tradition (Christian) with regard to funeral rituals and mourning processes.